Spatiotemporal analysis of prolonged and recurrent bovine tuberculosis breakdowns in Northern Irish cattle herds reveals a new infection hotspot. (February 2019) - Milne, G.M.; Graham, J.; Allen, A.; Lahuerta-Marin, A.; McCormick, C.; Presho, E.; Skuce, R.; Byrne, A.W.
Highlights: Prolonged and recurrent bovine tuberculosis cases cluster spatially in NI. Chronic infections are largely focused on areas where the disease burden is high. A new hotspot was identified associated with recurrent breakdowns. Abstract: Despite a state-led eradication programme, bovine tuberculosis (bTB) remains endemic in Northern Ireland (NI). Of particular concern are "chronic" prolonged and recurrent bTB breakdowns, which represent significant financial and administrative burdens. However, little is known regarding the spatiotemporal distribution of chronic breakdowns in NI. We therefore analysed both the spatial and spatiotemporal distributions of chronic bTB breakdowns between 2004 and 2014. Significantly positive values for Moran's Index of spatial autocorrelation were found, and Local Moran's I clustering was employed to assess for spatial associations in the number and prevalence of chronic bTB breakdowns across NI. Additional spatio-temporal analysis using SaTScan showed that the burden of chronic bTB infection tends to be found where bTB levels are already high. However, a novel hotspot was revealed wherein the prevalence of chronic breakdowns was higher than expected; this should be the subject of follow-up surveillance.